Plasma Levels of Vascular Endothelial Growth Factor and Selected Hemostatic Parameters in Association With Treatment Response in Multiple Myeloma. (18th February 2019) - Sokol, Juraj; Hrncar, Matej; Nehaj, Frantisek; Stasko, Jan
Multiple myeloma (MM) is a neoplastic plasma cell disorder characterized by the clonal proliferation of plasma cells in the bone marrow and presence of monoclonal protein in the blood or urine. Diverse hemostatic abnormalities have been reported in patients with myeloma which predispose the patient to bleeding and also thrombosis. The aim of this study was to measure the concentrations of serum levels of vascular endothelial growth factor, D-dimer, and von Willebrand factor in patients with newly diagnosed or relapsed multiple myeloma before treatment, during therapy, and after successful therapy. The working hypothesis was that all of these factors reflect the total body burden of tumor. Angiogenic and coagulation activity should therefore decrease after successful therapy. Our study indicates that selected prothrombotic abnormalities occur in patients with MM, which may contribute to the increased risk of venous thromboembolism observed in these patients. The levels of our 3 parameters were strongly elevated in patient with newly diagnosed MM and also in patients with clinical stage III based on International Staging System criteria. Furthermore, there was a correlation between prognostic disease stages in all study population. It would be appropriate to include angiogenic and coagulation parameters into prognostic parameters.